1998
DOI: 10.1002/(sici)1096-8628(19980106)75:1<88::aid-ajmg18>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous inferior and superior venae cavae with oculoauriculovertebral defect: Review of Goldenhar complex and malformations of left-right asymmetry

Abstract: We observed a girl with an interrupted, left inferior vena cava with hemiazygous continuation, bilateral superior venae cavae, heart defects, and sacral agenesis. She had macrostomia and bilateral ear tags and pits, as in oculoauriculovertebral defect. Maternal diabetes was present. The combination, which we call OAV-heterotaxia complex, supports the view that some cases of oculoauriculovertebral defect may be part of a midline field defect of blastogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…4 A vascular cause for the disruption of asymmetry in FAV has been suggested repeatedly in the literature. 2,5,6 The finding of a greaterthan-expected rate of some of the component anomalies of FAV among relatives of patients with FAV sequence suggests there may be a genetic contribution to its etiology, and it was suggested that there may be genetic factors involved in the vascular pathogenesis. 7,8 A number of patients have had chromosomal aberrations, but no consistent karyotypic anomaly has been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A vascular cause for the disruption of asymmetry in FAV has been suggested repeatedly in the literature. 2,5,6 The finding of a greaterthan-expected rate of some of the component anomalies of FAV among relatives of patients with FAV sequence suggests there may be a genetic contribution to its etiology, and it was suggested that there may be genetic factors involved in the vascular pathogenesis. 7,8 A number of patients have had chromosomal aberrations, but no consistent karyotypic anomaly has been found.…”
Section: Discussionmentioning
confidence: 99%
“…3 Disruption of blastogenesis during weeks 1-4 of gestation, when asymmetric development begins, is another commonly cited etiology, especially considering the many cases of discordant Goldenhar syndrome among monozygotic twins. 5,6 Recent systematic analysis showed a relationship between the anomalies seen in FAV and those of the vertebral anomalies, anal atresia, tracheo-esophageal fistula, and renal anomalies (VATER) association. 9 There is some evidence to suggest that disorders which arise during blastogenesis, including FAV sequence, VAC-TERL, and caudal regression syndrome, should be classified under the axial mesodermal dysplasia spectrum of disorders, as many cases were reported which overlap diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with OAVS‐HTX complex have recurrently been described, suggesting the possibility that OAVS in these patients represent a component of a malformation complex involving the organization of asymmetric structures (Caramia et a. ; Lin et al., ; Maat‐Kievit, Baraitser, & Winter, ; Volpe & Gentile, ). Interestingly, further testing of the patient using a multigene NGS panel including candidate genes for AVSD, HTX, and OAVS identified an additional missense variant in TBX1 gene, p.(Pro86Leu).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac, renal and central nervous system anomalies may be associated ( (Thommen et al, 1986;Gorlin et al, 1990a,b;Schrander-Stumpel et al, 1992;Kumar et al, 1993). Tracheo-oesophageal ®stula with or without oesophageal atresia (Sutphen et al, 1995) and lung malformations with hypoplasia to aplasia and abnormal segmentation were also described (Lin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%